(untitled) (International journal of artificial intelligence, 2026)
This article examines the stylistic features of humour in Gʻafur Gʻulom’s Shum Bola and Gerald Durrell’s My Family and Other Animals. The study focuses on how humour is created through childhood perspective, colloquial language, exaggeration, irony, satire, characterization, and comic situations. Although the two works belong to different literary and cultural traditions, both writers use humour not only to entertain readers but also to reveal character, expose human weaknesses, and present childhood as a unique way of understanding the world. The findings show that humour in Shum Bola is more closely connected with Uzbek folk speech, social satire, and the image of a clever mischievous child, while humour in My Family and Other Animals is mainly based on comic description, eccentric family members, animal imagery, and affectionate irony.